Learning Management of the Love-Based Curriculum at Madrasah Ibtidaiyah Negeri 2 Gorontalo Regency - Nurhikma Anugrahwati Lasaka; Said Subhan Posangi; Lian G. Otaya (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The implementation of the Love-Based Curriculum in Islamic schools requires effective learning management so that the values ​​of Panca Cinta can be systematically integrated into the learning process. However, studies explaining the relationship between the learning management function, the values ​​of Panca Cinta, and the factors influencing its implementation are still limited. This study aims to analyze the implementation of the Love-Based Curriculum learning management and identify supporting and inhibiting factors in Madrasah Ibtidaiyah Negeri 2 Gorontalo Regency. The study used a qualitative approach with a descriptive design involving 10 informants. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. Data validity was tested through source triangulation, technical triangulation, time triangulation, and member checking. The results showed that the implementation of the Love-Based Curriculum has been carried out through the functions of planning, organizing, implementing, monitoring, and evaluating integrated with the values ​​of Panca Cinta. Supporting factors include the leadership of the madrasah principal, teacher commitment, madrasah culture, collaboration with parents, and support for learning facilities, while inhibiting factors include differences in teacher understanding, limited learning time, diverse student characters, and suboptimal parental involvement. The novelty of this research lies in explaining the relationship between the function of learning management, the implementation of the Panca Cinta values, and supporting and inhibiting factors in implementing character-based learning in madrasahs.